Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages It is felt to be of great importance when teaching all Domestic Subjects whether in theory or practice that the institutional aspect should be kept in view from the beginning. Large-scale cookery should be a compulsory subject, and in its teaching emphasis should be laid on the best ways of preserving the nutritional value of the food as well as the palatability. It is suggested that the present course should be followed by further experience, of not less than six months, in cooking and catering in institutions approved by the College, and that at the end of such period the student should be able to obtain a certificate of proficiency in these subjects from the Cottege. C. Training of Dietitians. Objects.— The objects of the training should be to enable suitably qualified students to obtain such a knowledge of Nutrition and kindred subjects as will fit them for posts as dietitians in any kind of hospital. A student, therefore, should be able to calculate and supervise the preparation of meals of correct nutritional value for all types of normal healthy persons and be able to calculate and supervise the preparation and serving of special diets for all sick peopte. A dietitian should be able to instruct nurses, student-dietitians and out-patients. Courses Forming a Basis for Specialised Dietetic Training. 1. University degree courses in Domestic Science as recommended by the Hospital Sub-Committee. 2. University degree course in science including chemistry and physiology up to second M.B. standard, and three months' intensive cookery course at an institution approved by the Board of Education or the Instiutional Management Association. 3. Teachers' Certificate in Combined Domestic Subjects and also chemistry and physiology up to second M.B. standard. 4. State Registration in Nursing and three months' intensive cookery course at an institution approved by the Board of Education or the Institutional Management Association and chemistry and physiology up to second M.B. standard. 5. Institutional Management Certificate or Diploma after a training of not less than two years at an institution approved by the Board of Education and the Institutional Management Association. In view of the teaching work undertaken by dietitians it is recommended that students should take a short course in demonstrating, unless this has been already included in the previous training. Specialised Training in Dietetics. Facilities for special tuition in nutrition, chemistry, physiology and cookery should be available to make up for deficiencies in the various courses forming a basis for the specialised training. The specialised training should be given in a specially equipped department attached to 6 292/842/2/104